Analisis Loyalitas Berbasis Kepuasan Pelanggan Toko UKM Om Jeans Klaten - Andrias Tri Setya Budi (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
This research aims to know : product quality, service quality, the location, with satisfaction as intervening variabel toward customer loyalty. The results was bassed by the first hypothesis was accepted, so the second hypothesis was accepted, the third hypothesis was accepted, the fourth hypothesis was rejected, the fifth hypothesis was rejected, the sixth hypothesis was rejected, the seventh hypothesis was accepted, the eight hypothesis was accepted so the nineth hypothesis was accepted . to be conculuted : 1) product quality affectÂ toward customer satisfaction, 2) service quality influence toward customer satisfaction , 3) the location affect toward customer satisfaction , 4) Product quality does not affect the customer loyalty , 5) the quality of service did not affect toward customer loyalty , 6) Location not affect toward customer loyalty , 7) Customer Satisfaction affect toward customer loyalty , 8) Product quality, quality of service and the location of the simultaneous influence toward customer satisfaction , 9) Product quality, quality of service, location and customer satisfaction simultaneous effect toward customer loyalty.Key Words : Product quality, Quality of Service, Location, satisfaction, loyalty.